Development of a cost-effective, reusable, resuscitative hysterotomy task trainer for emergency medicine trainees - Christiana Agbonghae; Chelsea Rushnell; Brian Lorenzo; John D. Ehlers; Chad Scarboro; Lia Cruz; Sean Fox; Catherine Wares; Christyn Magill; Mark J. Bullard (Advances in Simulation)
Abstract We designed, developed, and constructed a reusable, durable, low-cost resuscitative hysterotomy (RH) task trainer with functional and structural fidelity for repetitive practice and education for emergency medicine trainees. The availability of commercial caesarean task trainers is limited, and their high cost often poses a barrier to training. Although similar procedures, RH and traditional caesarean section are unique, and to the authors’ knowledge there are currently no commercial task trainers specifically designed for RH. Current RH literature recommends completing the procedure within five minutes to improve the survival chances of both the fetus and the mother during active or imminent cardiac arrest. While RH is not a technically complex procedure relative to other procedures, it involves specific technical steps and requires clinicians to act decisively. Our RH task trainer was created using low-cost expired materials sourced from our hospital system and additional items purchased online. The RH task trainer was designed to be easily assembled, have minimal recurring material costs, and with quick set-up and clean-up for repetitive practice. When used within a simulation-based scenario, learners are also challenged with the decision to proceed with an RH; thus, providing experiential development of this decision-making step which is unparalleled in comparison to most traditional training formats. Overall, our RH trainer can be built for approximately 230 US dollars. The ability to create low-cost and easily accessible opportunities for repetitive practice of RH contributes to the limited pool of non-commercial RH task trainers, offering valuable experiential instruction for this unique, high-acuity, low-occurrence procedure. Brief description We developed a reusable, durable, low-cost resuscitative hysterotomy (RH) task trainer with functional and structural fidelity for repetitive practice and education for emergency medicine trainees at a tertiary care training hospital. Further, we aimed to create a task trainer that enhanced the cognitive and procedural skills required for performing RH within a high-stress clinical environment.